2010
DOI: 10.1002/lt.22072
|View full text |Cite
|
Sign up to set email alerts
|

Timing of hepatitis C antiviral therapy in patients with advanced liver disease: A decision analysis model

Abstract: Antiviral therapy for the treatment of hepatitis C virus (HCV) infection is used before and after liver transplantation. The objective of this study was to determine the most cost-effective timing for pegylated interferon/ribavirin therapy in patients with advanced liver disease infected with genotype 1 HCV. A Markov model was constructed to compare treatment strategies: (1) no treatment, (2) antiviral therapy in patients with compensated cirrhosis, (3) antiviral therapy in patients with decompensated cirrhosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 84 publications
1
51
0
2
Order By: Relevance
“…A recent study attempted to determine the most cost effective timing for AVT (PEG IFN and ribavirin) in advanced liver disease infected with HCV genotype 1 and concluded that treatment of patients with compensated cirrhosis was the most cost effective [117] . Four different treatment strategies in a hypothetical cohort of 4000, 55 years old, treatment naïve cirrhotics with a 17 year follow-up, were analyzed in a Markov model.…”
Section: Post-transplant Antiviral Treatmentmentioning
confidence: 99%
“…A recent study attempted to determine the most cost effective timing for AVT (PEG IFN and ribavirin) in advanced liver disease infected with HCV genotype 1 and concluded that treatment of patients with compensated cirrhosis was the most cost effective [117] . Four different treatment strategies in a hypothetical cohort of 4000, 55 years old, treatment naïve cirrhotics with a 17 year follow-up, were analyzed in a Markov model.…”
Section: Post-transplant Antiviral Treatmentmentioning
confidence: 99%
“…Prior to our analysis, cost-effectiveness of HCV treatment post OLT has only been studied by Saab et al in a North American cohort of patients [42,43]. In his first study [42], antiviral treatment with an estimated SVR of 20% resulted in a gain of 0.41 life-years compared with no treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Aim of another CEA of Saab et al [43] was to determine the best time point for Peg-IFN/RBV treatment in cirrhotic patients. Clinical and economic outcome of antiviral treatment of patients with compensated cirrhosis versus DC versus post OLT was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have assessed the use of interferon-based agents to treat HCV infection in patients while they wait for liver transplant and after transplant. 5 However, widespread use of interferon has been limited by safety, tolerability, and efficacy concerns. Moreover, interferon is contraindicated in patients with advanced liver disease, particularly when used with firstgeneration protease inhibitors.…”
Section: Introductionmentioning
confidence: 99%